(untitled) (Cambridge, 2009)
This is the very first book to distill the principles of complex adaptive systems and adaptive management into practical guidance for policymakers. It describes the concept of adaptive policymaking and presents seven tools for developing such policies. Based on hundreds of interviews with people impacted by policy and research of over a dozen policy case studies, this book serves as a pragmatic guide for policymakers by elaborating on these seven tools. It is an invaluable information resource for technical policymakers and politicians, as well as for those studying politics and international relations.
Keywords: Sustainable development,Environment policy,Adaptive natural resource management,Phát triển bền vững,Chính sách môi trường,Quản lý nguồn tài nguyên thiên nhiên thích hợp; Government policy,Chính sách của Chính phủ